Teaching Writing using PjBL in Maritime Higher Education - Yusi Rahmawati; Januarius Mujiyanto; Rudi Hartono; Hendi Pratama (International Conference on Science, Education, and Technology, 2023)
Implementation of PjBL (project-based learning) in vocational higher education is a very essential as regulated by the Indonesian government which is written down in Regulation of the Directorate General of Vocational Education Number 27 of 2022 about the guidance of implementation of project-based learning in vocational higher education. Project-based learning is a teaching method that is really helpful for an English lecturer in improving the students’ writing skills. It is because by using PjBL, the lecturer can train the students’ creativity in exploring their idea of making a written text, trying to find many ideas from many sources (both printed and electronic books), searching lots of videos, finding the best techniques to write some text genres. By using Project-based learning, the students can explore their creativity in learning writing skills such as expository, descriptive, persuasive, and narrative writing. In maritime higher education as a vocational higher education in Indonesia, implementing project-based learning hopefully can help the students to improve their ability in writing to prepare for their future when they are working in their workplace, they will be familiar and get easy to do their job. The topics of the texts can be made close to future workplace needs. The researchers hope that this research will be useful for language lecturers as an idea to develop their teaching model, especially in teaching English as a Foreign Language.